إدراك زراع الأراضي الجديدة لعمليات تدوير المخلفات الزراعية بقرية الناصر بشمال التحرير محافظة البحيرة - إبراهيم، خالد السيد محمد; جاد، معمر جابر; محمد، ابتسام ماهر (مركز البحث وتطوير الموارد البشرية - رماح, 2022)
استهدف البحث بصفة رئيسية التعرف على مستوى إدراك زراع الأراضي الجديدة بقرية الناصر بشمال التحرير لعمليات تدوير المخلفات الزراعية وتحويلها إلى أعلاف غير تقليدية، وتم اختيار عينة عشوائية بسيطة بواقع 40% من إجمالي الزراع بالقرية فبلغت العينة 162 مزارعا مبحوثا، وجمعت البيانات من خلال استمارة الاستبيان بالمقابلة الشخصية، وتم استخدام عدة أساليب إحصائية لعرض وتحليل البيانات وهي: النسب المئوية، والجداول التكرارية، والمتوسط الحسابي، والانحراف المعياري، ومعامل الارتباط البسيط لبيرسون، ومعامل الانحدار المتعدد. وأوضحت النتائج البحثية انخفاض كلا من إدراك ووعى المبحوثين بأهمية تدوير المخلفات الزراعية، وانخفاض مستوى إلمامهم بمراحل تدوير بعض المخلفات الزراعية وتحويلها إلى أعلاف غير تقليدية، وأظهرت النتائج البحثية وجود علاقة ارتباطية معنوية عند المستوى الاحتمالي (0.01)، (0.05) بين كلا من مستوى إدراك المبحوثين من الزراع لعمليات تدوير المخلفات الزراعية وكلا من المتغيرات التالية: حجم الحيازة الأرضية، والسعه الحيازية الحيوانية، وتعدد مصادر المعلومات الزراعية، وتوجه المزارع نحو بعض الممارسات المزرعية المستدامة، والسلوك البيئي الإيجابي وفسرت المتغيرات السابقة 33% من التباين الحادث في مستوى إدراك المبحوثين من الزراع لعمليات تدوير المخلفات الزراعية، وكانت أهم المشاكل التي ذكرها المبحوثون والتي تمثل عائقا أمام تدوير المخلفات هي: غياب الدور الإرشادي المعرفي والتدريبي في مجال تدوير المخلفات الزراعية، عدم معرفة المبحوثين بكيفية تطبيق بعض الأفكار، عدم توافر مستلزمات الإنتاج مثل غاز الأمونيا، نقص المعلومات عن كيفيه التنفيذ، عدم حاجه ورغبة المبحوثين للتطبيق، عدم توافر أماكن لتطبيق بعض الأفكار، استخدام الأعلاف التقليدية، صعوبة تطبيق بعض الأفكار. This research aimed to identify the level of Perception of the farmers at Al-Nasser village to the processes of recycling agricultural waste and converting it into unconventional fodder, A random sample of 162 respondents was selected to represent 40% of the total population (405 holders) in Al-Nasser village, questionnaire was designed to collect data via personal interview: percentages, frequency tables, arithmetic mean, standard deviation, simple correlation coefficient of Pearson, and multiple regression coefficients were used in analyzing the obtained research data. The research results showed a low level of perception of the respondents to the processes of recycling agricultural waste and converting it into unconventional fodders, and there is a significant correlation relationship at the probability level (0.01), (0.05) between each of the respondents' level of Perception of agricultural waste recycling processes and each of the following independent studied variables: the size of the land holding, the animal holding capacity, and the multiplicity of sources Agricultural information, directs the farmer towards some sustainable farming practices, and environmental behavior. The most important problems mentioned by the respondents, which represent an obstacle to waste recycling, were: the absence of an informative and training role in the field of agricultural waste recycling, the respondents' lack of knowledge of how to apply some ideas, the lack of resources, production requirements such as ammonia gas, the lack of information on the method of implementation, the lack of need and desire Respondents for the application, the lack of places to apply some ideas.
Keywords: الإرشاد الزراعي -- المخلفات الزراعية -- إعادة التدوير -- مصر